The Diversity of Macroscopic Fungi Species of The Wallacea in The Arboretum of BP2LHK Manado - Anita Mayasari; Margaretta Christita; Ady Suryawan (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2018)
Fungi have a vital role in ecological processes, as an indicator of health of an ecosystem, it is not only has the potency for medicine and food but also variety of unexplored potential. Arboretum has high potential for biological conservation including fungi species, so information on its diversity and potency are very important for the basis of its management. The purpose of this research was to explore the diversity of species and the potential of macroscopic fungi in the BP2LHK Manado Arboretum. Observations were conducted 8 times in May, June, and September 2016 using a cruise and an opportunistic method. The infromation of growth media, light intensity, and temperature were collected as a supporting data. The result showed that arboretum stored 48 species of macroscopic fungi with different characteristics. 39 species were identified, divided into 2 divisions, 6 classes, 9 orders, and 17 families, while the remaining 9 species were unidentified.. The results showed that the diversity of macroscopic species habitat were dominated by 31 species grown on necromass, 11 species grown on litter and 6 species grown on soil. Based on its potential, there were 2 species of toxic fungi, 1 species of edible and medicinal fungus, 2 species of edible fungi, 5 species with medicinal fungi, 19 species were not edible, and 19 species with unknown benefits.Keyword: arboretum, diversity, macroscopic fungi, Manado